Analisis Gaya Kepemimpinan Dosen dalam Metode Pemberian Tugas Terhadap Motivasi Belajar Mahasiswa Prodi Pendidikan Matematika di Universitas Labuhanbatu - Harahap, Amin; Azzahra, Luthfia; Pasaribu, Gita Sartika; Julianti, Julianti (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
The role of lecturers’ leadership is crucial in education, particularly in fostering student discipline and influencing learning motivation. Each lecturer demonstrates a different leadership style, and this study aims to examine how lecturers’ academic leadership styles in assigning tasks affect the learning motivation of students in the Mathematics Education Study Program at the University of Labuhanbatu. The background of this study is the concern that variations in assignments, guidance, and lecturer support may either strengthen or weaken student engagement. This study employed a quantitative approach using questionnaires distributed to the entire population of the 2024 cohort (N = 30), consisting of Class A students (n = 17, 56.67%) and Class B students (n = 13, 43.33%). Data were analyzed using SPSS Version 27, including validity tests, reliability tests, descriptive analysis, Pearson correlation, and simple linear regression. The results indicate a moderate positive correlation between lecturers’ leadership styles in assigning tasks and students’ learning motivation (r = 0.45, p 0.05). The linear regression analysis reveals that leadership style accounts for approximately 20% of the variance in learning motivation (R² ? 0.20), with clear communication and constructive feedback emerging as the main predictors. In conclusion, supportive and communicative leadership styles in task assignment can enhance students’ learning motivation. The implications suggest that lecturers are encouraged to design well-structured assignments, provide clear guidance, and follow up on student work constructively. Furthermore, it is recommended that lecturer training on motivational task-assignment strategies be implemented, along with the development of transparent assessment rubrics and structured feedback mechanisms to sustain learning motivation and support regular evaluation by the study program.ABSTRAKPeran kepemimpinan dosen sangat penting dalam pendidikan, terutama dalam mendisiplinkan mahasiswa dan memengaruhi motivasi belajar. Setiap dosen memiliki gaya kepemimpinan yang berbeda-beda, dan penelitian ini bertujuan membuktikan bagaimana gaya kepemimpinan akademik dosen dalam pemberian tugas memengaruhi motivasi belajar mahasiswa Program Studi Pendidikan Matematika Universitas Labuhanbatu. Latar belakangnya adalah kekhawatiran bahwa variasi tugas, cara pengarahan, dan dukungan dosen dapat memperkuat atau melemahkan keterlibatan mahasiswa. Penelitian menggunakan pendekatan kuantitatif dengan angket yang disebarkan ke seluruh populasi angkatan 2024 (N=30), terdiri dari mahasiswa kelas A (n=17, 56,67%) dan B (n=13, 43,33%). Data dianalisis menggunakan SPSS Versi 27, meliputi uji validitas, reliabilitas, deskriptif, korelasi Pearson, dan regresi linier sederhana. Hasil menunjukkan korelasi positif sedang antara gaya kepemimpinan dosen dalam pemberian tugas dan motivasi belajar (r=0,45, p0,05). Regresi linier mengungkapkan bahwa gaya kepemimpinan menjelaskan sekitar 20% variansi motivasi belajar (R²?0,20), dengan komunikasi jelas dan umpan balik konstruktif sebagai prediktor utama. Kesimpulan menyatakan bahwa gaya kepemimpinan suportif dan komunikatif dalam pemberian tugas dapat meningkatkan motivasi belajar. Implikasinya, dosen dianjurkan merancang tugas terstruktur, memberikan arahan jelas, dan menindaklanjuti hasil secara konstruktif. Dan disarankan dengan adanya pelatihan dosen tentang strategi penugasan motivasi, pengembangan rubrik penilaian transparan, serta mekanisme umpan balik terstruktur untuk keberlanjutan motivasi dan evaluasi berkala oleh program studi.